Maternal and fetal virilization by ovarian tumor Mother - Guerra García, Roger (2015)
The authors have studied a 23 year old female in whom an ovarian tumor developed during her 3rd pregnancy. The tumor was of the adrenal rest type and virilized both the mother and fetus, that was a pseudohermaphrodite girl; the virilization that occured in the mother receded three months after delivery, and the urinary excretion of Testosterone and 17-Ketosteroids were in the normal range at this point; however, an increase of the 17-Ks occured with the injection of HCG; the authors postulate that the tumor was hormone-dependent, and that the secreted androgens were able to cross the placenta and in this way to virilize the fetus.